Influence Customer Relationship Management and Timeliness of Service Towards Return Visit Interest at as Shafa Clinic Sidoarjo - Ekwandini, Dhona Rizky; Rahim, Agus Hadian; Veranita, Mira (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The health industry including hospitals is currently experiencing rapid development and facing various challenges. Every hospital or health clinic is required to provide the best service and in accordance with established standards and is expected to be able to reach all levels of society. The implementation of good service for patients is expected to increase the interest in returning visits made by patients to the clinic. One that can be applied by the Clinic is Customer Relationship Management (CRM) to maintain the relationship between the clinic and the patient. Patients who remain connected to the clinic and have an effective examination experience with punctuality are expected to increase the interest in returning visits. This study aims to determine the effect of Customer Relationship Management and timeliness of service on the interest in returning visits to the As Shafa Sidoarjo clinic. The study was conducted on 96 respondents who were employees of companies that collaborated with the As-Shafa clinic. This type of research is descriptive verification research. The statistical instrument used is regression analysis. Based on the results of the study, it shows that there is an influence of customer relationship management and timeliness of service on the interest in returning patients by 76.8% and the remaining 23.2% is influenced by other factors outside the study.